A Family of Single-Switch PWM Converters With High Step-Up Conversion Ratio - Ismail, E.H.; Al-Saffar, M.A.; Sabzali, A.J.; Fardoun, A.A. (IEEE transactions on circuits and systems. I, Regular papers, 2008)
A new family of a single-switch three-diode dc-dc pulsewidth-modulated (PWM) converters operating at constant frequency and constant duty cycle is presented in this paper. The proposed converters are different from the conventional dc-dc step-up converters, and they posses higher voltage gain with small output voltage ripples. Other advantages of the proposed converters include lower voltage stress on the semiconductor devices, simple structure, and control. Moreover, the reduced voltage stress on the diodes allows using Schottky diodes for alleviating the reverse-recovery current problem, as well as decreasing the switching and conduction losses. The principle of operation, theoretical analysis, and experimental results of one prototype rated 40W and operating at 94kHz are provided in this paper to verify the performance of this new family of converters.